Design and synthesis of new thiazolidinone/uracil derivatives as antiproliferative agents targeting EGFR and/or BRAFV600E - Alshammari, Mohammed B.; Aly, Ashraf A.; Youssif, Bahaa G. M.; Bräse, Stefan; Ahmad, Akil; Brown, Alan B.; Ibrahim, Mahmoud A. A.; Mohamed, Asmaa H. (Frontiers in Chemistry, 2022)
Thiourea derivatives of uracil were efficiently synthesized via the reaction of 5-aminouracil with isothiocyanates. Then, we prepared uracil-containing thiazoles via condensation of thioureas with diethyl/dimethyl acetylenedicarboxylates. The structures of the products were confirmed by a combination of spectral techniques including infra-red (IR), nuclear magnetic resonance (NMR), mass spectrometry (MS) and elemental analyses. A rationale for the formation of the products is presented. The newly synthesized compounds were evaluated for their in vitro antiproliferative activity against four cancer cell lines. The compounds tested showed promising antiproliferative activity, with GI50 values ranging from 1.10 µM to 10.00 µM. Compounds 3c, 5b, 5c, 5h, 5i, and 5j were the most potent derivatives, with GI50 values ranging from 1.10 µM to 1.80 µM. Compound 5b showed potent inhibitory activity against EGFR and BRAFV600E with IC50 of 91±07 and 93±08 nM, respectively, indicating that this compound could serve as a dual inhibitor of EGFR and BRAFV600E with promising antiproliferative properties. Docking computations revealed the great potency of compounds 5b and 5j towards EGFR and BRAFV600E with docking scores of −8.3 and −9.7 kcal/mol and −8.2 and −9.3 kcal/mol, respectively.